Profil Kemampuan Koneksi Matematis Mahasiswa Calon Guru dalam Menyelesaikan Masalah Matematika Berdasarkan Taksonomi Solo - Risma Firda Diana (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
This research aims to describe profil of preservice teacher’s mathematical connection ability in solving mathematical problem based on SOLO taxonomy. The approach of this research is qualitative with descriptive method. Respondent in this research is 29 Madrasah Ibtidaiyah Teacher Education students STAI Al-Fithrah Surabaya. This research uses mathematical connection test and interview guide to collect data. The result of this research show that the average mathematical connection ability of high-ability students is 85% with a very good category and that is at the level of multistructural to relational, the average mathematical connection ability of medium-ability students is 50,5% with enough category and that is at the level of unistructural to multistructural, and the average mathematical connection ability of low-ability students is 16% with a very low category and that is at the level of pre-structural until unistructural level.